2001
DOI: 10.1002/jcp.10018
|View full text |Cite
|
Sign up to set email alerts
|

CCKB/gastrin receptor mediates synergistic stimulation of DNA synthesis and cyclin D1, D3, and E expression in Swiss 3T3 cells

Abstract: In order to develop a model system for identifying signaling pathways and cell cycle events involved in gastrin-mediated mitogenesis, we have used high efficiency retroviral-mediated transfection of cholecystokinin (CCK)(B)/gastrin receptor into Swiss 3T3 cells. The retrovirally-transfected CCK(B)/gastrin receptor binds 125I-CCK-8 with high affinity (Kd = 1.1 nM) and is functionally coupled to intracellular signaling pathways including rapid and transient increase in Ca2+ fluxes, protein kinase C-dependent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 54 publications
(59 reference statements)
2
26
3
Order By: Relevance
“…Although the participation of G-17 in cellular proliferation is debatable, two recent studies have shown increased proliferation by G-17 in gastric cells (Hollande et al, 2001;Song et al, 2003). The fact that G-17 can induce cyclin D1 expression (Zhukova et al, 2001;Song et al, 2003) indirectly reveals its growth-promoting/ oncogenic function, since cyclin D1 functions as an oncogene in several kinds of tumor tissues (Motokura and Arnold, 1993), and new evidence suggests a role in invasion as well (Arato-Ohshima and Sawa, 1999;Jung et al, 2001). The CCK2 receptor (Watson et al, 2000) and gastrin (Bierkamp et al, 2002;Noble et al, 2003) have been implicated in regulating the invasion pathway as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the participation of G-17 in cellular proliferation is debatable, two recent studies have shown increased proliferation by G-17 in gastric cells (Hollande et al, 2001;Song et al, 2003). The fact that G-17 can induce cyclin D1 expression (Zhukova et al, 2001;Song et al, 2003) indirectly reveals its growth-promoting/ oncogenic function, since cyclin D1 functions as an oncogene in several kinds of tumor tissues (Motokura and Arnold, 1993), and new evidence suggests a role in invasion as well (Arato-Ohshima and Sawa, 1999;Jung et al, 2001). The CCK2 receptor (Watson et al, 2000) and gastrin (Bierkamp et al, 2002;Noble et al, 2003) have been implicated in regulating the invasion pathway as well.…”
Section: Discussionmentioning
confidence: 99%
“…A set of proteins known as cyclins (particularly cyclin D) contributes towards this process, by controlling G 1 /S transition, via regulating the activity of the cyclin-dependent kinases (CDK4 and CDK6) . Recent studies have shown increased expression of cyclin D1 in the presence of amidated gastrin (G-17) (Zhukova et al, 2001;Song et al, 2003), although the detailed mechanism(s) involved is unknown. In addition, H. pylori infection, which can lead to gastric cancer and is associated with hypergastrinemia also induces cyclin D1 transcription (Hirata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 controls G1/S transition by regulating the activity of the cyclin-dependent kinases (CDK4 and CDK6) (22). Gastrin is known to activate expression of both c-fos (44) and cyclin D1 (40,56). To enable focus on endogenous gene regulation, we measured cyclin D1 and c-fos mRNA, and used RNA interference to knock down ICER.…”
mentioning
confidence: 99%
“…Like G17, epidermal growth factor (EGF) also stimulates the proliferation of gastric epithelial cells (19,20), and recently, the G17-related peptide CCK has been shown to synergize with EGF to stimulate DNA synthesis ([ 3 H]thymidine incorporation), cyclin-D3 expression, and retinoblastoma protein phosphorylation in cells expressing both CCK 2 R and EGF receptors (21). EGF and the related growth factors transforming growth factor-␣ and amphiregulin bind to a family of receptors known as type I receptor tyrosine kinases.…”
mentioning
confidence: 99%